Prevalence and associated factors of malnutrition among school going adolescents of Dang district, Nepal - Bhattarai, Sigma (AIMS Public Health, 2019)
BACKGROUND: Malnutrition is a quiet emergency and one of the most widespread causes of morbidity and mortality among children and adolescent throughout the world; however there are very limited indications about the cause of malnutrition among adolescents. This study aimed to find out the prevalence and associated factors of malnutrition among school going adolescents of Dang district, Nepal. METHODS: School based descriptive cross-sectional research design among 510 school adolescents studying in grade 9 and 10 between ages 14–17 years on April–October 2017 was conducted in Dang district Nepal. Among total 130 secondary schools, 10 schools were selected; one government and one private from each 5 electoral constituency using multistage probability random sampling. RESULTS: The mean age and family size was 15.28 ± 0.77 and 5.25 ± 1.56 respectively. Among the total 25.7% of the adolescents are malnourished where 21.8% underweight, 3.1% overweight and 0.8% obese. After adjustment some of the variables such as religion (OR = 0.19; CI = 0.05–0.65, p = 0.008), family type (OR = 0.28; CI = 0.13–0.61, p = 0.001), school type (OR = 0.46; CI = 0.22–0.98, p = 0.044), earning status of family (OR = 4.52; CI = 1.44–14.16, p = 0.010), daily intake of green leafy vegetables (OR = 0.49; CI = 0.26–0.93, p = 0.031) and school sports (OR = 0.49; CI = 0.25–0.96, p = 0.040) were significantly associated with the underweight of adolescent. Similarly, variables such as gender (OR = 0.20; CI = 0.04–0.97, p = 0.046) and religion (OR = 9.75; CI = 2.24–42.39, p = 0.002) were significantly associated with the overweight/obesity of adolescent. CONCLUSION: Malnutrition was significantly higher among adolescents living in joint family, family having no earning status. Male adolescents were found more likely to be overweight and obesity. Hence to tie up the good nutrition it is recommended that integrated nutritional intervention and health related services should also be focused on adolescents.